2014
DOI: 10.1177/0020872814547437
|View full text |Cite
|
Sign up to set email alerts
|

The changing status and growth of social work education worldwide: Process, findings and implications of the IASSW 2010 census

Abstract: The dramatic growth in social work education is documented in the International Association of Schools of Social Work's 2010 census of institutions offering at least one degree program in social work. The census gathered data on program structure, personnel, student enrollment and curriculum from 473 respondents in the five IASSW regions. Half of the respondents reported requiring course content in social work history, values or ethics, and 20 percent of required courses are taught by non-social work educators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…While these are all important critiques, there is also opportunity to see and explore the potential of MOOCs within social work. While there has been some interest in exploring the role of MOOCs within the field, there has been little research on the particular role of MOOCs within social work (Barretta et al, 2016;Berzin et al, 2015, Gates & Walters, 2015Hawkins, Martin, McKay, & Pattanayak, 2017).…”
Section: Background Of Moocsmentioning
confidence: 99%
“…While these are all important critiques, there is also opportunity to see and explore the potential of MOOCs within social work. While there has been some interest in exploring the role of MOOCs within the field, there has been little research on the particular role of MOOCs within social work (Barretta et al, 2016;Berzin et al, 2015, Gates & Walters, 2015Hawkins, Martin, McKay, & Pattanayak, 2017).…”
Section: Background Of Moocsmentioning
confidence: 99%
“…Barretta-Herman's (2008) re-analysis of the 2005 IASSW membership survey, titled 'Meeting the Expectations of the Global Standards', re-confirmed consistency in social work educational programs across regions, though the eighth standard, which is concerned with cultural diversity, was not included in the study. However, another survey conducted by the IASSW in 2010 ( Barretta-Herman et al, 2014) found that the spread of social work programs makes the profession a potential weapon for delivering social justice content, globally. In addition, a few studies conducted that examined social work curricula were not linked to the GS.…”
Section: Review Of Curricular Research In Social Workmentioning
confidence: 99%
“…Ethno cultural diversity (E) symbolizes the need for social workers to acquire an in-depth understanding of their clients' culture and traditions through formal and informal education prior to provision of services. Human rights and social justice (H) symbolize the imperative for social workers to consider the rights of their multicultural clients within a social justice framework when providing services or conducting field research on client situations -for example, as related to the principles of the casework relationship by Biestek (1961) and professional social work values as stated in IASSW and IFSW (2004). Themes in strategic statements (T) symbolize how social work practice in multicultural settings should reflect the prevailing aims, objectives, mission, vision, and goals within their social contexts as reflected in their educational curricula, which by extension are reflecting the social policy of the country or community in which the practice occurs.…”
Section: Relative Similarities and Differences In Curricular Content mentioning
confidence: 99%
See 1 more Smart Citation
“…Gaps in meeting the GS included only half of the respondents reported requiring course content in social work history, values or ethics, and 20 per cent of the required courses were taught by non-social work educators. It was noted, however, that the expansion of social work programmes was indicative of social work's potential for the global promotion of social justice and development (Barretta-Herman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%